Unexplained Hematocrit Increase after Therapeutic Phlebotomy in a Patient with Marked Erythrocytosis. (11th August 2022) - Machhi, Rushad; Cunningham, Ashley M.; Hennrick, Kenneth; Schaser, Karen A.; Williams, Eliot C.; Rose, William Nicholas
Abstract : We report a patient with hereditary erythrocytosis who underwent a therapeutic phlebotomy and had a post-phlebotomy hematocrit that was higher than the pre-phlebotomy hematocrit. We could not discern a reason for this hematocrit increase after phlebotomy. Instead of performing another phlebotomy, we performed an automated red cell depletion via an apheresis instrument. This procedure is essentially a red cell exchange, but 5% albumin is used as the replacement fluid instead of red blood cells. The patient's hematocrit decreased from 80% to 39% after three consecutive daily red cell depletion procedures. We share our experience to report the unusual finding of a patient's hematocrit that increased with phlebotomy and to raise awareness of the red cell depletion procedure.